PENINGKATAN STATUS LANAL RANAI MENJADI LANTAMAL: STRATEGI INDONESIA SEBAGAI ANTISIPASI ANCAMAN CHINA DI NATUNA - Raden Mas Jerry Indrawan (Mandala: Jurnal Ilmu Hubungan Internasional, 2018)
The growing strength of China in all sectors, especially economy, and of course military, the country is increasingly aggressive in expanding its territory. As a result, the dispute in the South China Sea (SCS) between China and the five ASEAN countries, as well as Taiwan, spread to Indonesia, especially in Natuna. The Natuna Islands have an appeal to other countries because of its enormous natural resource and strategic location. To deal with the Chinese threat, which in case of war in Natuna will surely be done by sea, then this paper suggests to increase the status of Navy Base (Lanal) Ranai in Natuna into Navy Main Base (Lantamal). The escalation of threats from SCS makes Indonesia must have a strong sea defense base, facing directly to the SCS. So far, Indonesia only has 14 Lantamal, which is divided into two main command of the fleet, West Region Fleet Command (Koarmabar) and East Region Fleet Command (Koarmatim). With the vision of the World Maritime Fulcrum, 14 Lantamal with an area large as Indonesia, is certainly not enough. This paper also wants to see the link between the Navy and the Air Force in the concept of maritime based defense. This concept collaborates Navy and Air Force forces, due to geographical factors of the archipelagic state requires quick response. For that reason, the importance of synergy between Navy and Air Force seen from the role of Ranai Air Force Base in Natuna, Roesmin Nurjadin Air Force Base in Pekanbaru, and Supadio Air Force Base in Pontianak, to support Lantamal Ranai.